Mutation load and rapid adaptation favour outcrossing over self-fertilization - Morran, Levi T.; Parmenter, Michelle D.; Phillips, Patrick C. (Nature (London), 2009)
Two good reasons for sex One of the oldest questions in biology is, why are there separate sexes? More animals reproduce by cross-fertilization than by 'selfing', despite the cost of producing males and finding mates. Two advantages of cross-fertilization or outcrossing that could outweigh its cost are commonly suggested: the ability to evolve rapidly and avoidance of inbreeding, but it is hard to test for these experimentally. An experiment in which 'selfing' and 'outcrossing' variants of Caenorhabditis elegans nematodes were subjected to selective pressures now provides a practical test, and both potential standard explanations appear to have a role in promoting outcrossing. The tendency of organisms to reproduce by cross-fertilization, despite the advantages of self-fertilization and particularly the cost of males, is one of the oldest puzzles of evolutionary biology. Two advantages of outcrossing that could outweigh this cost have been suggested: the avoidance of inbreeding and an enhanced ability to adapt to environmental change. Here, the study of outcrossing in populations of Caenorhabditis elegans suggests that both of these explanations are correct. The tendency of organisms to reproduce by cross-fertilization despite numerous disadvantages relative to self-fertilization is one of the oldest puzzles in evolutionary biology. For many species, the primary obstacle to the evolution of outcrossing is the cost of production of males 1 , individuals that do not directly contribute offspring and thus diminish the long-term reproductive output of a lineage. Self-fertilizing (‘selfing’) organisms do not incur the cost of males and therefore should possess at least a twofold numerical advantage over most outcrossing organisms 2 . Two competing explanations for the widespread prevalence of outcrossing in nature despite this inherent disadvantage are the avoidance of inbreeding depression generated by selfing 3 , 4 , 5 and the ability of outcrossing populations to adapt more rapidly to environmental change 1 , 6 , 7 . Here we show that outcrossing is favoured in populations of Caenorhabditis elegans subject to experimental evolution both under conditions of increased mutation rate and during adaptation to a novel environment. In general, fitness increased with increasing rates of outcrossing. Thus, each of the standard explanations for the maintenance of outcrossing are correct, and it is likely that outcrossing is the predominant mode of reproduction in most species because it is favoured under ecological conditions that are ubiquitous in natural environments.